Environmental Health Thinking Design Inspiration of the Hadith of the Prophet SAW - Mumu Munajah; Engkos Kosasih (Gunung Djati Conference Series, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in life. This research method is qualitative through literature and field studies with the hadith design thinking approach. The results and discussion of this research include basic efforts to maintain environmental health during a pandemic, inspiring the example of the Prophet. in maintaining environmental health, and innovation in maintaining environmental health from an environmental ethics perspective. This research concludes that the hadith has an inspirational message in maintaining environmental health so that it can create health for human life.